A Ploidy Increase Promotes Sensitivity of Glioma Stem Cells to Aurora Kinases Inhibition. (19th August 2019) - Cilibrasi, Chiara; Guzzi, Andrèe; Bazzoni, Riccardo; Riva, Gabriele; Cadamuro, Massimiliano; Hochegger, Helfrid; Bentivegna, Angela
Abstract : Glioma stem cells account for glioblastoma relapse and resistance to conventional therapies, and protein kinases, involved in the regulation of the mitotic machinery (i.e., Aurora kinases), have recently emerged as attractive therapeutic targets. In this study, we investigated the effect of Aurora kinases inhibition in five glioma stem cell lines isolated from glioblastoma patients. As expected, cell lines responded to the loss of Aurora kinases with cytokinesis failure and mitotic exit without cell division. Surprisingly, this resulted in a proliferative arrest in only two of the five cell lines. These sensitive cell lines entered a senescent/autophagic state following aberrant mitotic exit, while the non-sensitive cell lines continued to proliferate. This senescence response did not correlate with TP53 mutation status but only occurred in the cell lines with the highest chromosome content. Repeated rounds of Aurora kinases inhibition caused a gradual increase in chromosome content in the resistant cell lines and eventually caused a similar senescence response and proliferative arrest. Our results suggest that a ploidy threshold is the main determinant of Aurora kinases sensitivity in TP53 mutant glioma stem cells. Thus, ploidy could be used as a biomarker for treating glioma patients with Aurora kinases inhibitors.